2022
DOI: 10.3390/toxins14120868
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Proposal for Botulinum Neurotoxin Injection Targeting the Platysma Muscle for Treating Platysmal Band and Jawline Lifting: A Review

Abstract: The platysma muscle is a thin superficial muscle that covers the entire neck and lower part of the face. The platysma muscle is the primary target muscle for botulinum neurotoxin injection therapy aimed at treating platysmal band and lower facial lifting. In the procedure of botulinum neurotoxin injection therapy, a lack of knowledge of the anatomy of the platysma muscle and the properties of botulinum neurotoxin can lead to side effects such as dysphagia, dysphonia, and weakness of the neck muscles. Anatomica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The authors concluded that a total of 40 units of BoNT-A should be injected at 20 points on both sides of the platysma band. For a jawline injection, they suggested a total of 40 units for 20 points with a subdermal injection [ 26 ]. Doan et al published a systematic review and meta-analysis to evaluate the efficacy and optimal dose of BoNT-A in the post-stroke lower extremity spasticity (PLES).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that a total of 40 units of BoNT-A should be injected at 20 points on both sides of the platysma band. For a jawline injection, they suggested a total of 40 units for 20 points with a subdermal injection [ 26 ]. Doan et al published a systematic review and meta-analysis to evaluate the efficacy and optimal dose of BoNT-A in the post-stroke lower extremity spasticity (PLES).…”
Section: Discussionmentioning
confidence: 99%
“…Facial aging is characterized by wrinkles, sagging skin, and a decrease in the amount of fat and elasticity in the face, particularly in the cheeks and surrounding tissue, which usually results in subzygomatic arch depression (Rewari et al, 2020). Wrinkles can be treated using botulinum neurotoxin injections, however, volume loss caused by the aging process is primarily treated with dermal filler injections (Yi et al, 2021; Yi, Lee, Hu, & Kim, 2022a, 2022b; Yi, Lee, Kim, Yoon, et al, 2022; Yi, Lee, Lee, Hu, et al, 2022). Subzygomatic arch depression may result in an appearance of premature aging and fatigue resulting from zygomatic arch and zygoma protrusion.…”
Section: Discussionmentioning
confidence: 99%
“…1 Non-invasive cosmetic procedures, such as thread lifting, dermal fillers and botulinum neurotoxin injections, have been proven to effectively address these issues. [2][3][4][5][6] Thread lifting, in particular, utilizes threads composed of materials such as polydioxanone (PDO), poly-L-lactic acid (PLLA) and etc. to lift and tighten sagging skin on the face.…”
Section: Introductionmentioning
confidence: 99%